Francisco Miró Quesada y la polémica sobre la China de Mao (1959-1960) - Guillermo Alexís Fernández Ramos (Nuevo mundo - Mundos Nuevos)
In 1959, Francisco Miró Quesada Cantuarias published La otra mitad del mundo, printed in two volumes, gave his testimony about his trip to the main socialist countries (the USSR and the People's Republic of China). His allegation is located in a first cycle of Peruvian travelers to China, after the Peruvian State reestablished commercial relations with the socialist countries of Eastern Europe and Asia. Other Peruvian travelers also left testimonial writings, but the one written by Miró Quesada was the one that had the greatest media impact. His book generated, before and after its publication, multiple responses in the form of articles (journalistic and academic) and public letters disseminated in different academic and journalistic media. Intellectuals from different perspectives were his detractors. In this regard, this article aims to study Miró Quesada's position with respect to Mao Zedong's China, as well as reconstruct the controversy it created.